Hide Tanning and Its Use in Taiga: The Case of the Orochen-Evenki Reindeer Herders and Hunters of Zabaikalye (East Siberia) - Donatas Brandišauskas (Journal of Ethnology and Folkloristics)
This article documents the way in which the Orochen-Evenki hunters and herders in northern part of Zabaikalye tan hides and produce gear in the post-Soviet era. Here, I wish to present the argument that it is difficult to understand the reviving of hide tanning in remote villages and the taiga without understanding how hunters and herders in this region adapt to the unstable post-Soviet environment. I suggest that hunters and herders aim to maintain their autonomy from goods and resources imported from cities, and, in spending little effort connecting with state powers in this way, securing their lives from socio-economic constraints.